Degassing, Crystallization and Rheology of Hawaiitic Lava Flows: the Case of the 1669 AD Eruption of Mount Etna (Italy). (2nd November 2022) - Lanzafame, Gabriele; Giacomoni, Pier Paolo; Casetta, Federico; Mancini, Lucia; Iezzi, Gianluca; Coltorti, Massimo; Ferlito, Carmelo
Abstract: Understanding lava flow dynamics during major effusive events is of paramount importance in volcanic areas characterized by a high risk of lava invasion. Mount Etna volcano (Sicily, Italy) has a long history of eruptions characterized by the emplacement of kilometer-wide lava fields, which have often reached the distal parts of the volcanic edifice, nowadays the location of numerous population centers. The 1669 eruption was one of the volcano's most important events in historic times due to the low altitude of the eruptive vent and the high volume of emitted products (607 ± 105 × 10 6 m 3 ), with lava flows that destroyed numerous villages located along their path. The flows reached the city of Catania, at a distance of >16 km from the emission point. In this work, we investigate the products of the 1669 eruption through geochemical, mineralogical, 2D and 3D textural analyses with the aim of reconstructing the degassing, crystallization and rheological history of the magma and lavas in pre- to post-eruptive conditions. Combining geothermobarometric and hygrometric models allowed us to estimate magmatic water content (4.1 wt.%) before the eruption, whereas the syn-eruptive crystal content (10 vol.% at the onset of flowing) was retrieved through the textural analysis of pyroclasts sampled from the near-vent fallout. Finally, crystallization and degassing occurring at surface conditions were reconstructed using the textural and mineralogical analysis of lavas. Results were integrated in a three-phase (melt + crystal + bubble) rheological model indicating that lava viscosity, at the onset of the eruption, was low enough (<3.51 log Pa s) to permit the development of a complex and extensive lava field. Flows reached numerous kilometers in length, thanks to the joint effects of lava tunneling, delayed crystal nucleation and growth, and the presence (up to 21.35 vol.%) of deformed bubbles. The combination of these processes maintained the high fluidity of the melt suspension, allowing the flow to arrive at considerable distances from the vent. Lastly, the results of this study highlight the necessity of an accurate real-time multi-analytical petrological characterization of active lavas during the monitoring of effusive eruptions, essential for reliable viscosity modeling of advancing flow units and therefore vital in predicting the direction of lava flows, especially in densely populated areas such as the southern flank of Mount Etna.